Analysis Of Modern Railway Power Quality Conditions With Inspection Methods To Mitigate Operating System Failures Referring To Regulations And Standard References - Damar Ravie Cahyadi; Iwa Garniwa Iwa Garniwa (Journal Of Social Science (JoSS), 2023)
Elevated stations or commonly called elevated stations have an electric power system with a main power supply of 20KiloVolt with a nominal voltage of 750volt and a station operating facility voltage of 380volt laying station. This research uses the inspection method by making observations by work instructions and instruction manuals for railway infrastructure maintenance studies. Some were identified as related to power quality issues with progression-appropriate inspections and appropriate instruction manuals. The main objective of this study is to prevent overvoltage interference problems by recommending risk mitigation through investigative and simulation analysis methods using Electric Transient and Analysis Program (ETAP) software that can help evaluate and estimate strategic steps by paying attention to regulations and standard references and detecting losses in operating pattern disturbances due to disruption of power quality conditions caused by overvoltage surges in the station traction substation system by investigation and simulation methods using Electric Transient and Analysis Program (ETAP) software. This overvoltage is carried out in the context of research on maintaining services to the public and preventing system failures by using risk mitigation and investigation and simulation methods using Electric Transient and Analysis Program (ETAP) software that pays attention to environmental, safety, technical, and economic aspects with regulations and standard references. This research is in the form of mitigation analysis and describes the losses that have an impact by looking at a power quality condition and the follow-up provided to prevent overvoltage and components of modern railway electric facilities.